Social arrangements. Kinship, descent and affinity in the mortuary architecture of Early Neolithic Britain and Ireland. (10th June 2022) - Fowler, Chris
Abstract: This article reassesses the social significance of Early Neolithic chambered tombs. It critically evaluates inferences about social organization drawn from tomb architecture and interpretations of kinship based on aDNA analyses of human remains from tombs. Adopting the perspective that kinship is a multifaceted and ongoing field of practice, it argues that the arrangement of tomb chambers was related to the negotiation of Early Neolithic kinship. Drawing together inferences about biological relatedness from aDNA analyses with interpretations of chamber arrangements, it suggests that variation in the architectural arrangements and sequential modification of chambered tombs relates to different ways of negotiating aspects of kinship, particularly descent and affinity. It presents interpretations of how kinship was negotiated at Early Neolithic tombs in different regions of Britain and Ireland and concludes that it is increasingly possible to gauge pattern and diversity in Neolithic negotiations of kinship, descent and affinity by combining different strands of evidence, including architectural arrangement.